Анализ ассоциаций полиморфных вариантов гена MTHFR с онкопатологиями у пробандов с псориазом и их родственников - Федота, А.М.; Беляева, Л.В.; Солодянкин, А.С.; Адмакина, А.В. (Фактори експериментальної еволюції організмів, 2013)
Aim. Research association of polymorphic variants of genes of folate metabolism with cancer in a ukrainian population had been investigated. Methods. Genealogical analysis of 68 probands and 440 relatives was carried out. Genomic DNA of 68 patients was analyzed by polymerase chain reaction. Results. Statistically significant higher cancer pathology burdened with native I–degree relatives of probands compared to genotypes CC–AA and TT–AA compared with population frequency. Probands with genotype CT–AC were the least burdened by native I–degree relatives with cancer pathology. Conclusion. The study of the frequency of malignant neoplasms in patients with psoriasis showed that among them persons with oncological diseases are not detected. It is known that cysteine is a powerful antioxidant, that, apparently, is one of the factors cancer protector not only for patients with psoriasis, but also for their native I–degree relatives as heterozygotes for single nucleotide polymorphisms C677T and A1298C MTHFR gene.